MALAYSIAN UNIVERSITY STUDENTS’ PERCEPTIONS AND KNOWLEDGE LEVEL OF INDUSTRIAL REVOLUTION 4.0 - Khairunesa Isa; Nurliyana Rosni; Sarala Thulasi Palpanadan (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Nowadays, humans live in a world of industrial revolution 4.0 that leads to many changes in daily life including in the context of employment and education. In order to endure the changes that exist, various challenges have to be faced and this situation requires sufficient preparation for youngsters especially students as they are the backbone of the country's development. Thus, this study was conducted to the examine students' perceptions of industrial revolution 4.0 and the level of students' knowledge in terms of the revolution. This quantitative study using survey technique was carried out on 173 students from three clusters of Malaysian public universities which were the research university, Focus University and comprehensive university. The findings showed that student perception and level of knowledge on industrial revolution 4.0 were low. However, the respondents were found to be willing to improve their knowledge and other skills related to the Industrial Revolution 4.0 demand. The findings were hoped to motivate the academic system to enhance their strategy and approach to prepare students towards industrial revolution needs